2006
DOI: 10.1051/eas:2006036
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Equilibrium Structure of CDM Halos

Abstract: N-body simulations find a universal structure for the halos which result from the nonlinear growth of Gaussian-random-noise density fluctuations in the CDM universe. This talk summarized our attempts to derive and explain this universal structure by analytical approximation and simplified models. As an example, we show here that a 1D spherical infall model involving a fluid approximation derived from the Boltzmann equation can explain not only the halo density profile but its phase-space density profile, as we… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
14
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 134 publications
(271 reference statements)
11
14
1
Order By: Relevance
“…The difference of TIS with our analysis is that we consider all non-singular solutions of the modified Emden equation (32) and not only the specific TIS one. This model is in a very good agreement with simulations and observations [77], at least outside the inner regions of the cluster. In the inner regions the TIS model predicts a soft core, however collisionless Nbody simulations of dark matter haloes predict a cusp, rather than a core.…”
Section: Galaxy Clusters In the Presence Of Dark Energysupporting
confidence: 87%
“…The difference of TIS with our analysis is that we consider all non-singular solutions of the modified Emden equation (32) and not only the specific TIS one. This model is in a very good agreement with simulations and observations [77], at least outside the inner regions of the cluster. In the inner regions the TIS model predicts a soft core, however collisionless Nbody simulations of dark matter haloes predict a cusp, rather than a core.…”
Section: Galaxy Clusters In the Presence Of Dark Energysupporting
confidence: 87%
“…Thus, even for spherical objects the spins k 3 and k 4 will not be identical. In fact, Shapiro et al (2004) pointed out that the presence of infalling matter acts as a surface pressure even for collisionless DM. The surface term leads to 2T þ U > 0.…”
Section: Spinmentioning
confidence: 99%
“…A good match between their models and the NFW profile requires a fine tuning of initial conditions. Shapiro et al (2004) also explored the importance of CDM accretion history using one-dimensional simulations and very similar arguments to ours. Unfortunately, they use a fluid approach that solves Jeans-like moments of the collisionless Boltzmann equation and, presumably, the elimination of any possible asymmetric velocity distribution prevented them from finding our ρ ∝ r −1 result.…”
Section: Resultsmentioning
confidence: 76%
“…White & Zartisky 1992;Ryden 1993;Sikivie et al 1997;Subramanian et al 2000;Subramanian 2000;Hiotelis 2002;Le Delliou & Henriksen 2003;Shapiro et al 2004;Barnes et al 2005). Applying the collisionless Boltzmann equation to self-similar gravitational collapse, Subramanian (2000) and Subramanian et al (2000) demonstrated that tangential velocities are required to obtain an inner profile that is shallower than that of a singular isothermal sphere.…”
Section: Summary and Discussionmentioning
confidence: 99%
See 1 more Smart Citation